2017
DOI: 10.1186/s12864-017-3485-0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide diversity inflation as a genome-wide response to experimental lifespan extension in Drosophila melanogaster

Abstract: BackgroundEvolutionary theory predicts that antagonistically selected alleles, such as those with divergent pleiotropic effects in early and late life, may often reach intermediate population frequencies due to balancing selection, an elusive process when sought out empirically. Alternatively, genetic diversity may increase as a result of positive frequency-dependent selection and genetic purging in bottlenecked populations.ResultsWhile experimental evolution systems with directional phenotypic selection typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 77 publications
1
24
0
Order By: Relevance
“…), whereas the protein‐tyrosine phosphatase receptor gene Ptp10D has been previously identified as a candidate locus in another EE study of Drosophila longevity (Michalak et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), whereas the protein‐tyrosine phosphatase receptor gene Ptp10D has been previously identified as a candidate locus in another EE study of Drosophila longevity (Michalak et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of our significant longevity (E-P) loci showed a significant overlap with candidates identified by both Carnes et al (2015) and Fabian et al (2018) development or function (Ace, Ptp10D, nmo, Pura, CG32373, and spg), which is interesting considering the role of neuronal processes and neuroendocrine signaling in the regulation of lifespan (Tatar 2004;Alcedo et al 2013). For example, the acetylcholinesterase gene Ace is known to affect lifespan in C. elegans (Xue et al 2007), whereas the protein-tyrosine phosphatase receptor gene Ptp10D has been previously identified as a candidate locus in another EE study of Drosophila longevity (Michalak et al 2017). Among the remaining overlapping candidates, which overlap with only one of the other E&R datasets, we identified several genes (e.g., Doa, Beadex, and cappuccino) that play a role in gonad development or reproduction (Quinlan 2013;Zhao et al 2013; Kairamkonda and Nongthomba 2014)-they might thus represent loci with pleiotropic effects on fecundity and lifespan, which co-evolved consistently in all four studies.…”
Section: Across Independent Experimentsmentioning
confidence: 99%
“…In each generation of selection, the 50% with the highest stress tolerance was selected from 300 pairs. A sixth group selected for longevity was also established, but since it did not involve an ecological stressor, genomic variation in this group was investigated in a separate study (Michalak, Kang, Sarup, Schou, & Loeschcke, ). The selection procedures are described in detail elsewhere (Bubliy & Loeschcke, ; Malmendal et al., ), and the phenotypic data are highlighted by Figures and in Bubliy & Loeschcke, .…”
Section: Methodsmentioning
confidence: 99%
“…Over many generations, flies breeding at old 766 age would have accumulated more TEs in the genome than populations reproducing 767 early in life. Supporting this hypothesis, it has been demonstrated that most TE 768 families had a higher rate of insertions in the ovaries of older relative to young P-769 element induced dysgenic hybrids, even though at the same time fertility was restored 770 were also repeatably larger in late-breeding populations across four experiments 777 (Table S4), although we have not ruled out that this was driven by genetic drift or 778 balancing selection as proposed by one study (Michalak et al 2017). our expression analysis confirms that many genes associated with transcriptional and 783 post-transcriptional TE silencing tend to be upregulated with age.…”
Section: Is Reproduction At Old Age Associated With An Increased Te Cmentioning
confidence: 88%